Análise temporal da estabilidade das margens e área de preservação permanente no rio Jacuí, Rio Pardo, RS: o caso da mineração de areia - (:unkn) unknown (Universidade Federal do Pampa, 2023)
The use of satellite imagery for problem-solving related to the Earth's physical environment, especially regarding visual impacts, is widely employed in various fields of knowledge (Exact and Earth Sciences, Agricultural, Biological etc.). In the environmental sphere, it serves as a tool for monitoring extractive activities such as mining, agriculture, livestock, forestry, etc. Especially due to being an indirect and cost-effective method compared to direct field methods. In mining companies, the impacts caused by resource extraction are as evident as their importance in global technological advancement. The extraction of sand from riverbeds also faces socio-environmental conflicts, requiring intensive monitoring for the conservation of natural resources. In these cases, various environmental impacts are known, with the most relevant ones being the instability of river banks and Permanent Preservation Areas, leading to serious harmful consequences such as the loss of productive areas and local biodiversity, fauna displacement, and siltation of water bodies, among others. The study area is located in the middle course of the Jacuí River, in the municipality of Rio Pardo, Rio Grande do Sul, with the State Foundation for Environmental Protection Henrique Luis Roessler being the supervisory body responsible for environmental licensing in RS. This work consists of spatial analysis using orbital images, specific software, and satellites as a temporal comparison of marginal modifications and Permanent Preservation Areas along the river. Supported by direct data: measurements with a portable turbidimeter of the upstream and downstream waters of the sand extraction areas, search for field truths, image recording and photographic documentation of pre-defined areas with the highest impact identified by Remote Sensing analysis; and indirect data: comparative orbital images, and the Zoning for sand extraction activity conducted by State Foundation for Environmental Protection Henrique Luis Roessler, and satellite images with specific band. Proposes to generate a simplified impact matrix for the creation of two semiqualitative thematic maps, east and west, of the slope stability and Permanent Preservation Areas zoning. Ultimately, by integrating these data, the study aims to elucidate the likely impacts of sand extraction on the intensification of marginal erosion rates and Permanent Preservation Areas, highlighting the importance of understanding the natural processes of river dynamics and erosion in these impact studies. It serves as a data support for future research within this context.
Keywords: SIG; Erosão marginal; APP; Extração de areia; Meio ambiente; GIS; Marginal erosion; Permanent Preservation Areas; Sand extraction; Environment; CNPQ::CIENCIAS EXATAS E DA TERRA